2019
DOI: 10.5005/jp-journals-10024-2638
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Vestibule Access Tunneling with Platelet-rich Fibrin Membrane for the Treatment of Gingival Recession

Abstract: Aim:The aim of this study was to introduce the less invasive vestibule access tunneling in combination with platelet-rich fibrin (PRF) membrane for gingival recession treatment. Materials and methods: Seven subjects with Miller's class I or II buccal gingival recession were selected for this study. All subjects were treated with mucogingival surgery using the less invasive vestibule access tunneling in combination with PRF membrane. Clinical examination performed on each subject and the height of gingival rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, this technique ensures a premature esthetic result and satisfactory healing because adequate blood supply is necessary to maintain the stability of the gingival attachment to the root surface. 39 Skierska et al 40 reported satisfactory values for RC (93.31%) and CRC (87.43%) after 2 years of follow-up using the TT associated with CTG in a retrospective study. However, limited gains in RC, CRC, KT width, and gingival thickness were observed on both sides in our study, with a reduction in these gains after 16 months.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, this technique ensures a premature esthetic result and satisfactory healing because adequate blood supply is necessary to maintain the stability of the gingival attachment to the root surface. 39 Skierska et al 40 reported satisfactory values for RC (93.31%) and CRC (87.43%) after 2 years of follow-up using the TT associated with CTG in a retrospective study. However, limited gains in RC, CRC, KT width, and gingival thickness were observed on both sides in our study, with a reduction in these gains after 16 months.…”
Section: Discussionmentioning
confidence: 94%
“…Mucogingival surgery is a procedure that can be used to repair gingival recession; this surgery focuses mostly on improving the appearance and functionality of the patient's mouth. In addition to increasing the zone of attached gingiva, maintaining the normal shape of the soft tissue, and providing enough gingival thickness with normal color, mucogingival surgery can cover exposed root surfaces up to the CEJ [8], [9]. There are four basic techniques for root coverage therapy:…”
Section: Discussionmentioning
confidence: 99%
“…An internal bevel incision is used during the tunneling procedure from above the gingival margin in the recessionprone area. The interdental papillae were then affected by extending a supraperiosteal partial thickness flap with strong dissection 3-5 mm laterally and apically to the recession area [8]. The gingival profile makes it challenging to regulate mechanical instrumentation throughout the tunneling technique and to appropriately detach the junctional epithelium from its attachment to the root surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation